2020
DOI: 10.3390/land9100372
|View full text |Cite
|
Sign up to set email alerts
|

Land Use/Land Cover Changes and the Relationship with Land Surface Temperature Using Landsat and MODIS Imageries in Cameron Highlands, Malaysia

Abstract: Mountainous regions are more sensitive to climatic condition changes and are susceptible to recent increases in temperature. Due to urbanization and land use/land cover (LULC) issues, Cameron Highlands has been impacted by rising land surface temperature (LST) variation. Thus, this study was carried out to explore the impact of the LULC change on LST in the Cameron Highlands from 2009 to 2019 using remote sensing images acquired from Landsat 7 ETM+, Landsat 8 Operational Land Imager (OLI/TIRS), and Moderate Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 60 publications
3
33
0
Order By: Relevance
“…At local scales, the increase in urban infrastructure increases albedo, decreases evapotranspiration, and generates the UHI phenomenon [5,71,72], while at regional scale, forest cover keeps the temperature relatively constant, and the climatic variations could be associated with regional or global climatic events or phenomena (El Niño and the Southern Oscillation, or global climate change [73][74][75]). This is similar to other tropical cities as Beijing, Changchun, and Hangzhou, China [1,8,11], Cameron Highlands, Malaysia [76], or Shiraz, Iran [77]. In all cases, UHI phenomena are associated with the extension of the urban area, type of structures and material, density housing, and presence of areas with continuous vegetation within the city.…”
Section: Discussionsupporting
confidence: 72%
“…At local scales, the increase in urban infrastructure increases albedo, decreases evapotranspiration, and generates the UHI phenomenon [5,71,72], while at regional scale, forest cover keeps the temperature relatively constant, and the climatic variations could be associated with regional or global climatic events or phenomena (El Niño and the Southern Oscillation, or global climate change [73][74][75]). This is similar to other tropical cities as Beijing, Changchun, and Hangzhou, China [1,8,11], Cameron Highlands, Malaysia [76], or Shiraz, Iran [77]. In all cases, UHI phenomena are associated with the extension of the urban area, type of structures and material, density housing, and presence of areas with continuous vegetation within the city.…”
Section: Discussionsupporting
confidence: 72%
“…It has been observed that the intensification of agricultural expansion, settlement expansion, human activities, forest product harvesting, and mining are key contributors to land use in Cameron Highlands ( Fig 4 ). There are also the factors of government policies on the expansion of agriculture to eliminate poverty in the region; human population growth; and advancements in plantation technologies, arable soil, and climate suitability, which are the various underlying drivers of land use changes [ 6 , 29 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…A preliminary study analyzing the connection between LULC and land surface temperature (LST) for the study area was extensively discussed by How Jin Aik et al [ 35 ] using multi-temporal satellite images of Landsat 7 and 8 to provide a better understanding of the LULCC in the highland regions. The results illustrated an increment of total urban area by 1.7% in 10 years, while farmland and agriculture rose by 7.71% significantly.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations